2020
DOI: 10.1101/2020.07.24.220244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Beta Cell Mass Expansion In Vivo With A Harmine and Exendin-4 Combination: Quantification and Visualization By iDISCO+ 3D Imaging

Abstract: Since all diabetes results from reductions in numbers of functional pancreatic beta cells, beta cell regenerative drugs are required for optimal and scalable future diabetes treatment. While many diabetes drugs are in clinical use, none increases human beta cell numbers. We have shown that a combination of the DYRK1A inhibitor, harmine, with the GLP1 receptor agonist, exendin-4, markedly increases human beta cell proliferation in vitro. However, technological limitations have prevented assessment of human beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Recently, several groups have demonstrated that small molecule drugs that inhibit the kinase DYRK1A ( d ual t y rosine– r egulated k inase 1A) are able to induce adult human β cells to proliferate, to increase in numbers, and to enhance their differentiation and function ( 7 17 ). Even higher rates of proliferation can be achieved by combining DYRK1A inhibitors with peptide agonists of the GLP1 receptor such the GLP1 7–36 peptide, or more stable synthetic analogs, such as exendin-4, liraglutide, semaglutide, and others, all in current widespread use in T2D ( 10 , 12 ). The combination of a DYRK1A inhibitor, harmine, together with exendin-4, increases human β cell mass in immunodeficient mice transplanted with human islets by 700% over 3 months of treatment, while also reversing diabetes ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several groups have demonstrated that small molecule drugs that inhibit the kinase DYRK1A ( d ual t y rosine– r egulated k inase 1A) are able to induce adult human β cells to proliferate, to increase in numbers, and to enhance their differentiation and function ( 7 17 ). Even higher rates of proliferation can be achieved by combining DYRK1A inhibitors with peptide agonists of the GLP1 receptor such the GLP1 7–36 peptide, or more stable synthetic analogs, such as exendin-4, liraglutide, semaglutide, and others, all in current widespread use in T2D ( 10 , 12 ). The combination of a DYRK1A inhibitor, harmine, together with exendin-4, increases human β cell mass in immunodeficient mice transplanted with human islets by 700% over 3 months of treatment, while also reversing diabetes ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even higher rates of proliferation can be achieved by combining DYRK1A inhibitors with peptide agonists of the GLP1 receptor such the GLP1 7–36 peptide, or more stable synthetic analogs, such as exendin-4, liraglutide, semaglutide, and others, all in current widespread use in T2D ( 10 , 12 ). The combination of a DYRK1A inhibitor, harmine, together with exendin-4, increases human β cell mass in immunodeficient mice transplanted with human islets by 700% over 3 months of treatment, while also reversing diabetes ( 12 ).…”
Section: Introductionmentioning
confidence: 99%